Cartilage Morphological and Histological Findings After Reconstruction of the Glenoid With an Iliac Crest Bone Graft. Issue 5 (April 2018) - Auffarth, Alexander; Resch, Herbert; Matis, Nicholas; Hudelmaier, Martin; Wirth, Wolfgang; Forstner, Rosemarie; Neureiter, Daniel; Traweger, Andreas; Moroder, Philipp
Background: The J-bone graft is presumably representative of iliac crest bone grafts in general and allows anatomic glenoid reconstruction in cases of bone defects due to recurrent traumatic anterior shoulder dislocations. As a side effect, these grafts have been observed to be covered by some soft, cartilage-like tissue when arthroscopy has been indicated after such procedures. Purpose: To evaluate the soft tissue covering of J-bone grafts by use of magnetic resonance imaging (MRI) and histological analysis. Study Design: Case series; Level of evidence, 4. Methods: Patients underwent MRI at 1 year after the J-bone graft procedures. Radiological data were digitally processed and evaluated by segmentation of axial images. Independent from the MRI analysis, 2 biopsy specimens of J-bone grafts were harvested for descriptive histological analysis. Results: Segmentation of the images revealed that all grafts were covered by soft tissue. This layer had an average thickness of 0.87 mm compared with 1.96 mm at the adjacent native glenoid. Of the 2 biopsy specimens, one exhibited evident hyaline-like cartilage and the other presented patches of chondrocytes embedded in a glycosaminoglycan-rich extracellular matrix. Conclusion: J-bone grafts are covered by soft tissue that can differentiate into fibrous and potentially hyaline cartilage. This feature may prove beneficial for delaying the onset of dislocation arthropathy of the shoulder.